The Effect of Social Media Marketing Through Brand Awareness on Brand Loyalty on Instagram @digitalbusiness.upi - Muhammad Safiq (Universitas Pendidikan Indonesia (UPI), 2023)
University of Education Indonesia also opened a Digital Business Study Program, which not only conducts conventional socialization, but also through social media Instagram @digitalbusiness.upi, however, based on engagement data from the Instagram account @digitalbusiness.upi has decreased by 70.3%, on the other hand the Digital Business Study Program competitors from other universities who also use social media marketing. This study uses a quantitative descriptive analysis method which then the data is obtained from distributing questionnaires using a non-probability sampling method with purposive sampling. So that the sample used was 180 students of the Digital Business Study Program. The data analysis used is descriptive and inferential data analysis techniques using Partial Least Square (PLS) with SmartPLS 3.2.9 software. The results of this study indicate (1) Brand awareness has a positive and significant effect on brand loyalty with a path coefficient of 0.527. (2) Social media marketing has a positive and significant effect on brand awareness with a path coefficient of 0.562. (3) Social media marketing has a positive and significant effect on brand loyalty with a path coefficient of 0.364. (4) Social media marketing has a positive and significant effect on brand loyalty through brand awareness with a path coefficient of 0.296. Social media marketing and brand awareness have a contribution of 62.10% in influencing brand loyalty, while the remaining 37.90% is influenced by other variables.